Immobilized Saccharomyces cerevisiae as a potential aflatoxin decontaminating agent in pistachio nuts - Rahaie,S. (2010)
In this study, we investigated the binding ability of Saccharomayces cerevisiae to aflatoxin in pistachio nuts. The obtained results indicate that S. cerevisiae has an aflatoxin surface binding ability of 40% and 70% (with initial aflatoxin concentrations of 10 and 20 ppb) in the exponential phase. Acid treatments increase this ability to approximately 60% and 73% for the two concentrations of aflatoxin, respectively. Heat treatments also enhance surface binding to 55% and 75%, respectively. Binding appears to be a physical phenomenon that saturates within the first 2-3 hours of the process. The obtained results indicate that yeast immobilization for toxin reduction on aflatoxin-contaminated pistachios had no effect on qualitative characteristics, such as color, texture, and peroxide value. Yeast cells, viable or nonviable, are effective for aflatoxin binding, and this property could lead to a promising solution to aflatoxin contamination in high-risk foods.